Seeking for Religion, Mexican Female Muslim Converts - Mondragon Meza, Gabriela Aurora (International journal of Latin American religions, 2025)
This study is about online religious information seeking behavior (ISB) among Mexican female Muslim converts using the sense-making theory developed by Dervin (1983). The respondents were fourteen Mexican female Muslim converts living in Mexico, where they face the day-to-day challenges of how to be a Muslim in a non-Islamic environment. These are further compounded by the misconception created by the mass media about Islam and its followers. The research objectives are as follows: (1) To investigate the motivation to start the online religious ISB, (2) to identify the information needs, and (3) to explore their information use and in overall to describe the experience of Mexican female Muslim converts in their process of online religious ISB. A qualitative methodology was used, utilizing online narrative interviews through WhatsApp. ATLAS.ti software was used for data management and analysis. It was concluded that the converts are at one particular situation embedded by time and space. This situation can be an impactful experience that takes them to the path of search of meaning which evolves to the information needs. Then, they enter into a process of information seeking driven by their background and cultural context where they belong. Then, they start using the information, making mental and physical changes, and applying the information they analyzed and reflected upon it. The present research adds to the existing body of knowledge in communication, ISB, Internet studies, and in the context of minority Muslims.